2017
DOI: 10.1155/2017/9327136
|View full text |Cite
|
Sign up to set email alerts
|

High Neutrophil-to-Lymphocyte Ratio Predicts Cardiovascular Mortality in Chronic Hemodialysis Patients

Abstract: The neutrophil-to-lymphocyte ratio (NLR) is a novel simple biomarker of inflammation. It has emerged as a predictor of poor prognosis in cancer and cardiovascular disease in general population. But little was known of its prognostic value in chronic hemodialysis (HD) patients. Here we investigated the association between NLR and cardiovascular risk markers, including increased pulse pressure (PP), left ventricular mass index (LVMI) and intima-media thickness (IMT), and mortality in HD patients. Two hundred and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 44 publications
5
61
0
2
Order By: Relevance
“…In patients on prevalent hemodialysis, NLR was also associated with all-cause mortality [25]. We recently reported that NLR was also associated with allcause and cardiovascular mortality in patients on hemodialysis [26]. NLR was found to be an independent predictor of left atrium mechanical function and atrial electromechanical delay times in patients with ESRD receiving peritoneal dialysis or hemodialysis [27].…”
Section: Discussionmentioning
confidence: 98%
“…In patients on prevalent hemodialysis, NLR was also associated with all-cause mortality [25]. We recently reported that NLR was also associated with allcause and cardiovascular mortality in patients on hemodialysis [26]. NLR was found to be an independent predictor of left atrium mechanical function and atrial electromechanical delay times in patients with ESRD receiving peritoneal dialysis or hemodialysis [27].…”
Section: Discussionmentioning
confidence: 98%
“…The increased NLR values are associated with poor outcomes for various types of cancers, including colorectal cancer, esophageal cancer, gastric cancer, non‐small‐cell lung cancer, ovarian cancer, and pancreatic cancer . Importantly, It has been reported that the NLR value was an independent prognostic parameter in cardiovascular disease, nodular sclerosis Hodgkin lymphoma, bladder cancer, advanced pancreatic cancer . Moreover, the elevated NLR value has been shown to correlate with worse prognosis in patients with HCC who underwent transcatheter arterial chemoembolization, radiofrequency, resection, or liver transplantation .…”
Section: Introductionmentioning
confidence: 99%
“…Li et al showed that high neutrophil/ lymphocyte ratio can predict cardiovascular mortality in chronic hemodialysis patients [31]. The dialysis duration in their study was not correlated with cardiovascular mortality (correlation coefficient = 0.055, P = 0.369).…”
Section: Discussionmentioning
confidence: 76%
“…In another study by Losito et al demonstrated that dialysis duration was one of the predictor of cardiovascular mortality. But the OR was borderline (OR: 1.002, 95% CI: 1.001 -1.004, P = 0.006) [31]. The controversy might be due to not enough duration of follow up and other confounding factors which were correlated with dialysis duration and masked its impact on cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 97%